2015
DOI: 10.2215/cjn.08760914
|View full text |Cite
|
Sign up to set email alerts
|

Obstructive Sleep Apnea Severity and Overnight Body Fluid Shift before and after Hemodialysis

Abstract: Background and objectives Obstructive sleep apnea is associated with significantly increased cardiovascular morbidity and mortality. Fluid overload may promote obstructive sleep apnea in patients with ESRD through an overnight fluid shift from the legs to the neck soft tissues. Body fluid shift and severity of obstructive sleep apnea before and after hemodialysis were compared in patients with ESRD.Design, setting, participants, & measurements Seventeen patients with hemodialysis and moderate to severe obstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
39
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(45 citation statements)
references
References 40 publications
0
39
0
Order By: Relevance
“…using ODI of 15 as a cutoff point. Ogna et al . further demonstrated that gender was a weak predictor of SDB in the HD population (OR: 0.72; CI: 0.12‐4.20, P >.2) and should not be used to screen for SDB in this population.…”
Section: Risk Factors For Sleep‐disordered Breathing In Hemodialysis mentioning
confidence: 99%
See 3 more Smart Citations
“…using ODI of 15 as a cutoff point. Ogna et al . further demonstrated that gender was a weak predictor of SDB in the HD population (OR: 0.72; CI: 0.12‐4.20, P >.2) and should not be used to screen for SDB in this population.…”
Section: Risk Factors For Sleep‐disordered Breathing In Hemodialysis mentioning
confidence: 99%
“…For example, insomnia is more female predominant due to changes in hormones (menstrual cycle or menopause), and SDB is more often found in males due to larger pharyngeal length . In the HD population, gender difference does not correlate to poor sleep quality nor to the presence of SDB . Tada et al .…”
Section: Risk Factors For Sleep‐disordered Breathing In Hemodialysis mentioning
confidence: 99%
See 2 more Smart Citations
“…Lins et al showed that atrial natriuretic peptide concentrations decrease post dialysis in those patients whose BP responded to ultrafiltration [29]. Other reported mechanisms include increased arterial stiffness [30], renin-angiotensin-aldosterone system activation [31], sympathetic hyperactivity [32,33], endothelial dysfunction [34,35], sleep apnoea [36] and use of erythropoiesis-stimulating agents (ESAs) [37,38].…”
Section: Hypertensionmentioning
confidence: 99%